Meta Analisis Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Kemampuan Matematis Siswa - Reinaldo Pasaribu Pasaribu; Hendri Prastyo (LPPM Universitas Advent Indonesia, 2022)
This study aims to describe: (1) the effect of the guided inquiry learning model on the overall mathematical ability of students, (2) the effect of the guided inquiry learning model on the components of mathematical ability, (3) the effect of the guided inquiry learning model on mathematical abilities based on education level, ( 4) The influence of the guided inquiry learning model on students' mathematical abilities based on the material being taught. The population in this study is research that has been published nationally with a range of 2017 to 2021. The sampling technique used purposive sampling and obtained 20 studies that matched the criteria. The data analysis technique uses Cohen's d effect size analysis. The results of the study: (1) Overall, the guided inquiry learning model increased students' mathematical abilities with an effect size value of 0.79 on the moderate effect criteria, (2) The guided inquiry learning model gave the greatest influence on mathematical communication skills with an effect size value of 1.35 with a large effect criterion, (3) The use of the guided inquiry learning model looks more suitable to be applied in junior high school because it has a greater influence in improving students' mathematical abilities with an effect size value of 0.84 in the large effect criterion, (4) Learning model Guided inquiry is more influential in improving students' mathematical abilities with an effect size value of 1.62 with a large effect criterion on junior high school statistics material.